Religion, solidarity and identity: a comparative study of four South African schools with a religious affiliation - Cawood, Anthony Robin (School of Education, 2018)
This thesis explores how schools with a religious affiliation recruit religion in school culture and the formal curriculum (both curriculum content and pedagogic method) and how this relates to the pedagogic identities they project. An overarching concern of the thesis is to understand how the character of the affiliated religion relates to the privileging of particular forms of solidarity and identity. This explorative, multiple case study is located in four independent schools in South Africa, each with an official affiliation to a particular religious community. The sample comprises a co-educational charismatic Protestant school, a liberal Catholic school, a traditional-Orthodox Jewish school and a conservative Muslim school. The study foregrounds Bernstein’s (1990, 2000) suggestion that a sociologically important characteristic of religions is the way they constitute the relation between the 'inner’ self and the 'outer’ social world. The thesis looks to Bernstein’s (1975, 2000) theory that the ideology inherent in pedagogic discourse constitutes particular instantiations of power and control (related to Bernstein’s concepts of classification and framing respectively) that structure a school’s curriculum and pedagogic methods. The analysis of school culture utilises Bernstein’s (1975) theory of ritual and identity is explored in relation to Bernstein’s (2000) taxonomy of pedagogic identities. Furthermore, Durkheim’s (1915, 1960) concept of mechanical and organic solidarity and his theory of the sacred and the profane provide the primary conceptualizations of social order. The qualitative analysis of interview data (obtained from students, teachers, principals and religious leaders), policy documentation and direct observation shows significant differences between the schools relating to the recruitment of the affiliated religion in curriculum, pedagogy and ritual. The analysis suggests that the schools affiliated to religions in which the inner and the outer are dislocated (the Protestant and Catholic school), recruit the affiliated religion in a way that predominantly privileges a moral order in which the student is weakly related to a collective and individualised values and relations are emphasised (organic solidarity). Conversely, the schools in the sample affiliated to religions in which the inner is not dislocated from the outer (the Jewish and Muslim school), recruit the affiliated religion in a way that privileges strong identification of the student to a collective (mechanical solidarity). However, the analysis suggests that the form of solidarity related to the recruitment of the affiliated religion at the schools is not always the only form of solidarity privileged. More specifically, the analysis shows that components of the instructional order 'unordered’ by the affiliated religion may result in a layering of different forms of solidarity within the same school. The analysis implies that the schools project different pedagogic identity modes enabled by particular instantiations of power and control related to the privileged form/s of social solidarity. The major finding of the thesis is that the character of the affiliated religion, in terms of its constitution of the inner and the outer, relates to the form of social solidarity privileged by the school’s recruitment of religion, which, in turn, enables the projection of particular pedagogic identities. This thesis makes a contribution to a growing body of literature that vi challenges the idea that 'religious schools’ are homogenous. It provides a theoretical methodology for exploring differences and similarities between 'religious schools’ across different religions and suggests a sociologically important source of variance in 'religious schools’ in general.